Metal Metabolism in Aquatic Environments 1998
DOI: 10.1007/978-1-4757-2761-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ecological factors on accumulation of metal mixtures

Abstract: A very large number of experimental studies in aquatic ecotoxicology have been devoted to the assessment of metal uptake in different classes of living organisms. Most of them are based on analysis of single toxicants, despite the fact that under field conditions the biota is generally exposed to multicontaminant pollution. In addition to producing a direct response in biota, a toxic metal can also act by interfering with other metal ions or elements. Thus, the concurrent presence of two or more metallic conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…As a result of their chemical affinities, Cd and Zn may share similar uptake pathways into organisms (Rainbow, 1997). It has been similarly observed that in many molluscan species, exposure to the non-essential metal Cd had no effect on Zn accumulation; whereas exposure to essential metal Zn had an antagonistic effect on Cd accumulation (Amiard-Triquet and Amiard, 1998). Littorinids are generally considered to be good indicators of contamination with dissolved Cd (Stenner and Nickless, 1974;Manga and Hughes, 1981;Bryan et al, 1983).…”
Section: Discussionmentioning
confidence: 91%
“…As a result of their chemical affinities, Cd and Zn may share similar uptake pathways into organisms (Rainbow, 1997). It has been similarly observed that in many molluscan species, exposure to the non-essential metal Cd had no effect on Zn accumulation; whereas exposure to essential metal Zn had an antagonistic effect on Cd accumulation (Amiard-Triquet and Amiard, 1998). Littorinids are generally considered to be good indicators of contamination with dissolved Cd (Stenner and Nickless, 1974;Manga and Hughes, 1981;Bryan et al, 1983).…”
Section: Discussionmentioning
confidence: 91%
“…Interaction between Cd and Zn kinetics have been demonstrated but are often inconsistent and contradictory (44). For example, Cd uptake decreases (not statistically significant) in M. galloprovincialis at 100 µg of Zn L -1 (45).…”
Section: Resultsmentioning
confidence: 99%
“…Uptake of metals in mixtures may demonstrate competitive and noncompetitive inhibition and in some cases enhanced uptake . The type of interaction depends on the metals involved, their external concentration, availability and exposure scenario, length of exposure, studied species, and examined organs , . The existence of metal−metal interactions occurring at low, environmentally relevant concentrations has been reported for different crustacean , and fish species , .…”
Section: Introductionmentioning
confidence: 99%